Public-legal problems of formation and development of engineering education in Central Asia in the context of the new program of industrial-innovative development on the example of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article deals with training in the field of engineering and technology staff. Problems of economic growth is closely linked to the development of such an institution as the engineering education. The lack of any detailed study of this issue creates difficulties in the development of both engineering education and the adaptation of the training process. And restrictions are largely related to the protection of the interests of individual groups and empowerment of individual government agencies create awareness about the unfair competition which is peculiar to specific areas of public policy.Key words: engineering education, public-legal regulation, certification, accreditation, training.